Do Geopolitical Risk and Economic Uncertainty Harm Bank Credit ? Evidence From the Indonesian Bank - Nadia, Linda Putri; Krisnanda, Krisnanda; Sa'adah, Wahidatun Nailis; Yasin, Rozaq Muhammad (Jurnal Riset Ilmu Ekonomi, 2024)
This study examines how economic uncertainty and geopolitical risks affect credit growth. It analyzes data from 47 Indonesian banks from 2008 to 2022.  The study employs purposive sampling to select 47 Indonesian banks based on loan and financial data availability, resulting in 456 observation data. Economic uncertainty and geopolitical risk significantly reduce overall bank credit growth. Further investigation into different proxies of independent variables derived from various regression model specifications has a robust result indicating the negative impact on credit growth. The analysis highlights that lagged economic uncertainty and geopolitical risk values continue to impact current credit growth dynamics, emphasizing their persistent effects. Robustness tests further support these findings, confirming the negative impact of lagged economic uncertainty and geopolitical risk on credit growth. Based on the results, the study contributes to the literature on the effects of economic uncertainty and geopolitical risks on credit growth, supporting the real options theory and the precautionary motive hypothesis. It offers key policy recommendations: reduce economic uncertainty and geopolitical risk, monitor and manage their persistent impacts, strengthen financial system resilience through robust regulation, and promote sustainable economic growth via infrastructure investment, innovation, and structural reforms.